2014
DOI: 10.1155/2014/953094
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mood and Anxiety Disorders on Incident Hypertension at One Year

Abstract: Background. Studies assessing the association between psychological factors and hypertension have been equivocal, which may reflect limitations in the assessment of psychological factors. Purpose. To assess the relationship between mood and anxiety disorders, measured using a psychiatric interview, and 1-year incident hypertension. Methods. 197 nonhypertensive individuals undergoing exercise stress testing at baseline provided follow-up data at 1 year. Baseline assessments included a structure psychiatric inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 52 publications
0
31
0
8
Order By: Relevance
“…Major depressive episode or dysthymia were associated with 20% greater odds of hypertension in the following year after adjusting for confounders including other psychiatric disorders. In the MOMSI study (described above), no association was found between mood disorders and incident hypertension [38]. Though inconsistent with previous findings, this may be due to the limited power (n cases =16) or to the heterogeneity of mood disorders category, which unlike other studies included bipolar disorder.…”
Section: Psychological Risk Factors For Incident Hypertensionmentioning
confidence: 92%
See 3 more Smart Citations
“…Major depressive episode or dysthymia were associated with 20% greater odds of hypertension in the following year after adjusting for confounders including other psychiatric disorders. In the MOMSI study (described above), no association was found between mood disorders and incident hypertension [38]. Though inconsistent with previous findings, this may be due to the limited power (n cases =16) or to the heterogeneity of mood disorders category, which unlike other studies included bipolar disorder.…”
Section: Psychological Risk Factors For Incident Hypertensionmentioning
confidence: 92%
“…In another study in the meta-analysis, researchers completed an psychiatric interview among 190 middle-aged Canadian adults (MOMSI study) and considered risk of developing hypertension (n cases =16) over the following year [38]. Individuals with anxiety disorders had 7.25 higher odds (95%CI=1.90-27.74) of having physician-diagnosed hypertension or antihypertensive medication at follow-up, after adjusting for standard covariates, psychotropic medication, and comorbid mood disorder.…”
Section: Psychological Risk Factors For Incident Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with anxiety have a higher risk of hypertension than those without [39, 40]. Previous studies have reported that prevalence of anxiety is 9.5% in hypertensive patients [41].…”
Section: Discussionmentioning
confidence: 99%